Influence of FOXP3 gene polymorphisms on the risk of preeclampsia: a meta‐analysis and a bioinformatic approach - Mohammad Karimian; Saeedeh Ghazaey Zidanloo; Danial Jahantigh (Clinical and Experimental Hypertension, 2022)
Background and aim Preeclampsia (PE), a multifactorial disorder, is the main cause of maternal mortality and morbidity. Genetic polymorphisms in key proteins involved in the immune system may change the risk of PE risk. In this study, we examined the association of two rs2232365 and rs3761548 common polymorphisms of the FOXP3 immune response gene with PE susceptibility by a meta-analysis which was followed by an in-silico analysis. Materials and methods Through a systematic search in databases including PubMed, MEDLINE, Google Scholar, and Science Direct, we find eligible studies for meta-analysis. Some bioinformatics tools were used to detect the impact of rs2232365 and rs3761548 polymorphisms on the FOXP3 gene function. Results Our data revealed that there is a significant association between rs3761548 polymorphism and decreased risk of PE. In addition, we observed a significant association between rs2232365 and increased risk of mild preeclampsia. Also, our bioinformatic analysis showed that both rs2232365 and rs3761548 polymorphisms could affect FOXP3 gene function. Conclusion Based on our findings, the rs3761548 genetic variation could be a protective factor against PE risk. While the rs2232365 polymorphism may be a genetic risk factor for mild preeclampsia. Therefore, as a preliminary study, these genetic variations could be considered molecular biomarkers for PE disorder.